Climate change and ageing in ectotherms. (24th August 2020) - Burraco, Pablo; Orizaola, Germán; Monaghan, Pat; Metcalfe, Neil B.
Abstract: Human activity is changing climatic conditions at an unprecedented rate. The impact of these changes may be especially acute on ectotherms since they have limited capacities to use metabolic heat to maintain their body temperature. An increase in temperature is likely to increase the growth rate of ectothermic animals, and may also induce thermal stress via increased exposure to heat waves. Fast growth and thermal stress are metabolically demanding, and both factors can increase oxidative damage to essential biomolecules, accelerating the rate of ageing. Here, we explore the potential impact of global warming on ectotherm ageing through its effects on reactive oxygen species production, oxidative damage, and telomere shortening, at the individual and intergenerational levels. Most evidence derives primarily from vertebrates, although the concepts are broadly applicable to invertebrates. We also discuss candidate mechanisms that could buffer ectotherms from the potentially negative consequences of climate change on ageing. Finally, we suggest some potential applications of the study of ageing mechanisms for the implementation of conservation actions. We find a clear need for more ecological, biogeographical, and evolutionary studies on the impact of global climate change on patterns of ageing rates in wild populations of ectotherms facing warming conditions. Understanding the impact of warming on animal life histories, and on ageing in particular, needs to be incorporated into the design of measures to preserve biodiversity to improve their effectiveness. Abstract : An increase in temperature is likely to increase the growth rate of ectothermic animals, and may also induce thermal stress via increased exposure to heat waves. Here, we suggest that global warming can potentially impact on ectotherm ageing through its effects on reactive oxygen species production, oxidative damage, and telomere shortening, at the individual and intergenerational level. We also discuss candidate mechanisms that could buffer ectotherms from the potentially negative consequences of climate change on ageing. Finally, we propose some potential applications of the study of ageing mechanisms for the implementation of conservation actions.